2021
DOI: 10.1177/10901981211003510
|View full text |Cite
|
Sign up to set email alerts
|

Communication Campaigns to Support the Use of Nutritional Warnings: Different Messages for Different People?

Abstract: Communication campaigns are expected to contribute to increase the efficacy of nutritional warnings. In this context, the aims of the present work were (a) to evaluate how citizens perceive different types of messages for a communication campaign and (b) to determine if personal characteristics such as gender, age, and educational level, as well socioeconomic and nutritional status, moderate how citizens perceive such campaign messages. A series of graphic pieces were designed for each of the following three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Consumers are generally not aware of evolutionary mechanisms driving their food choices; hence, making them aware of these mechanisms can facilitate healthier eating (Ares et al, 2021;Kessler, 2009, p. 247). Four strategies that policymakers can embrace to help consumers make informed food choices are as follows: (1) listing calories of all items in the restaurant menus; (2) labeling foods in such a way that makes information about unhealthy ingredients salient; (3) conducting public education campaigns highlighting OLD MINDS, NEW MARKETPLACES 13 health risks associated with eating unhealthy foods; and (4) demarketing companies that promote unhealthy products by publicly exposing their business practices (Kessler, 2009, pp.…”
Section: Educate the Publicmentioning
confidence: 99%
“…Consumers are generally not aware of evolutionary mechanisms driving their food choices; hence, making them aware of these mechanisms can facilitate healthier eating (Ares et al, 2021;Kessler, 2009, p. 247). Four strategies that policymakers can embrace to help consumers make informed food choices are as follows: (1) listing calories of all items in the restaurant menus; (2) labeling foods in such a way that makes information about unhealthy ingredients salient; (3) conducting public education campaigns highlighting OLD MINDS, NEW MARKETPLACES 13 health risks associated with eating unhealthy foods; and (4) demarketing companies that promote unhealthy products by publicly exposing their business practices (Kessler, 2009, pp.…”
Section: Educate the Publicmentioning
confidence: 99%
“…In Uruguay, a recent study showed the need to create different types of communication campaign messages according to gender, age and nutritional status of the target population when promoting the use of WLs [30], showing that diverse approaches are necessary in the population segments since each one responds differently to the WLs. Informing and educating children and adolescents to adequately use the WLs when choosing their food is essential, especially when ultra-processed products are highly available in school environments [31].…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Marketing literature has established numerous state and trait predictors of consumer behavior (Belk, 1975;Haugtvedt et al, 1992;Vinson et al, 1977). With respect to healthy (vs. unhealthy) food choices, the mainstream literature focuses on proximate explanations such as quality expectations, nutrition information, and certification (Grunert, 2002;Nikolova & Inman, 2015;Sigurdsson et al, 2020;Thøgersen et al, 2019), but also in-store product placement (Sigurdsson et al, 2011(Sigurdsson et al, , 2014, individual differences (Otterbring, 2019;Rojas-Rivas et al, 2020), and message framing (Ares et al, 2020;Ares et al, 2021), as well as shopping habits (Machín et al, 2020), visual imagery (Banovic & Otterbring, 2021; OLD MINDS, NEW MARKETPLACES 4 Otterbring & Shams, 2019), and visual attention to food products (Folwarczny et al, 2019;Gidlöf et al, 2021;Wästlund et al, 2018). However, to fully understand human decision-making, it is crucial to also consider ultimate explanations.…”
Section: Analyzing Consumer Food Choices Through An Evolutionary Lensmentioning
confidence: 99%